Mastering Windows 365. - Christiaan Brinkhoff; Sandeep Patnaik; Morten Pedholt; Scott Manchester; Ken Pan; Phil Gerity; PACKT (GB: Packt, 2024)
Unlock advanced IT Pro skills for Windows 365, Intune, Intune Suite, Microsoft Copilot, AI PCs, and more-build expertise from the ground up! Key Features Practical guide to deploying and managing Windows 365 cloud PCs with real-world scenarios Detailed coverage of advanced features, including Microsoft Intune, Graph API, and Security Copilot Insights from Microsoft experts who played a key role in shaping Windows 365 and Azure Virtual Desktop Book Description Windows 365 Cloud PC continues to evolve, integrating AI-driven management, enhanced security, and expanded capabilities to provide a seamless cloud-based Windows experience. This second edition builds on the foundation of the first, incorporating new content on Intune Suite, Copilot+ AI PCs, Windows App, and advanced security with Security Copilot to help IT professionals deploy, manage, and optimize Windows 365 Cloud PCs effectively. This edition expands beyond the basics, covering Intune Suite's role in optimizing and securing deployments, new methods for application management and delivery, and insights into Windows 365 Link for hybrid cloud environments. You'll also explore AI-powered administration with Security Copilot, providing intelligent security management and automation. Written by experts from the Windows 365 product team and a Microsoft MVP, this book provides practical guidance, best practices, and real-world insights to help you master modern Windows cloud management. Whether you're working with Windows 365, Intune Suite, or AI-powered administration, this guide equips you with the latest tools and strategies to stay ahead in cloud computing. What you will learn Deploy and configure Windows 365 cloud PCs for a seamless cloud experience Manage and secure cloud PCs using Microsoft Intune Automate workflows with Microsoft Graph to improve efficiency Strengthen security with Copilot in Intune and Microsoft security protocols Optimize performance, diagnose issues, and troubleshoot cloud environments Explore future advancements in cloud computing and Windows 365 Secure Windows 365 Cloud PC connections using best practices Who this book is for This book is for IT administrators, architects, consultants, and CIOs looking to leverage and design Windows 365 cloud PCs effectively and train for the Modern Desktop MD-102 Administrator certification. This book is also for anyone seeking to move their virtualization or Windows endpoints to the cloud with ease. Basic understanding of modern management based on Microsoft Intune and Microsoft 365 is required.
Data in extended ASCII character set.
Mode of access: Internet.